A Comprehensive Solution for Development of Large Scale Grid-Connected PV Generation in China. Issue 1 (January 2015) - Qiankun, Wang
To combat climate change and fulfill the national target of having 15% of primary energy from non-fossil fuels by 2020, China's central government is making every effort to promote PV generation, especially in the context of deteriorating export markets for China's PV industry, resulting from anti-dumping and anti-subsidy campaigns launched by United States and European Union. PV generation PV generation is set to boom in coming years in China. Although there is ambitious planning of building large scale ground-mounted PV plants in the Northwest of China, more than half of the installations are expected to be customer-sited small scale distributed systems. Because PV generation, particularly customer-sited PV systems represents a totally new pattern of power production and consumption. China's electricity system, which has been originally designed for centralized power delivery, is not fully prepared to accommodate large scale PV generation from the technical point of view. Besides, governmental policies and operational regulations are not able to match the need of these new comers. This paper works out a comprehensive solution for integration of large scale distributed PV, which consists of technical strategy, regulatory strategy and policy strategy. Firstly, electricity grids and PV systems should be directionally technically adapted to each other. oGrid friendly PV plants" requires that PV plants should be equipped with advanced technologies to improve the visibility, controllability and predictability, bringing the performance of PV plants increasingly close to that of conventional power plants. Secondly, with high penetration of distributed PV generation, grid dispatch centers should have necessary monitoring and control over these dispersed generating systems, which are supposed to follow the instructions issued by grid operators. Thirdly, incentive polies should be in accordance with national medium-and long term planning, with consideration of minimizing social cost. Policies should also be foreseeable and persistent for all the investors. Based on the framework of the comprehensive solution for PV generation, this paper elaborates major experience drawn from Germany with high PV penetration and illustrates how Germany has successfully integrated large scale distributed PV systems from the technical, regulatory and policy aspect respectively. Finally, it comes up with relevant recommendations for the development of PV generation in China: to speed up the process of establishing and improving the system of technical requirements, to draw up and release detailed operational rules on distributed PV generating systems and replace unified FIT for ground-mounted systems with differentiated FIT. Distributed customer-sited PV systems should be promoted by subsidizing the self-consumed electricity in the form of RMB cent per kWh.